Karakterisasi Dan Analisis Pengolahan Greywater Menggunakan Karbon Aktif - Saputra, Muhammad Ramadhan; Andrio, David; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The growth of population will increase clean water demand. One of several way that can be done is by treating wastewater and reuse it as an alternative source. This research aims to determine the characteristics of greywater and analyze the removal chemical oxygen demand (COD), oil and grease using activated carbon. The result of this study show the COD, oil and grease in 397 mg/L and 152 mg/L. Keywords: Activated Carbon, Greywater